2006
DOI: 10.1007/s00467-006-0051-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-related congenital nephrotic syndrome with diffuse mesangial sclerosis

Abstract: This case report describes congenital nephrotic syndrome in a 2-month-old girl associated with cytomegalovirus infection. Histological examination on renal biopsy showed diffuse mesangial sclerosis and cytomegalic inclusion bodies in the tubular cells and in some glomeruli. Cytomegalovirus (CMV) polymerase chain reaction (PCR) titer in serum was high. Remission of pulmonary and renal symptoms was achieved with ganciclovir in 3 weeks. No recurrence of proteinuria was observed during the follow-up period of 14 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 12 publications
0
28
1
Order By: Relevance
“…Although not all of the cases published are well documented, they are described as being congenital nephrotic syndrome. All of the reported cases were treated with ganciclovir, which was discontinued in one patient due to its side effects [19][20][21]. There are also two reports of pediatric patients, a 3-month old baby and a 14-year-old boy, with interstitial nephritis associated with CMV infection [22,23].…”
Section: Discussionmentioning
confidence: 92%
“…Although not all of the cases published are well documented, they are described as being congenital nephrotic syndrome. All of the reported cases were treated with ganciclovir, which was discontinued in one patient due to its side effects [19][20][21]. There are also two reports of pediatric patients, a 3-month old baby and a 14-year-old boy, with interstitial nephritis associated with CMV infection [22,23].…”
Section: Discussionmentioning
confidence: 92%
“…Frishberg et al [4] reported a case of mutated podocin manifesting as CMV-associated CNS and proposed that CMV infection was only a secondary finding. Recently, Besbas et al [5] reported a 2-month-old girl with CMVassociated CNS and diffuse mesangial sclerosis in her renal biopsy. Her proteinuria disappeared and her clinical status improved after ganciclovir treatment.…”
Section: Discussionmentioning
confidence: 98%
“…However, the causal relationship between CMV infection and CNS has still not been unfolded. There are still few reports documenting that such an association exists [4,5]. Frishberg et al [4] reported a case of mutated podocin manifesting as CMV-associated CNS and proposed that CMV infection was only a secondary finding.…”
Section: Discussionmentioning
confidence: 98%
“…Proteinuria in infancy is rare and may occur due to congenital nephrotic syndrome, diffuse mesangial sclerosis, Denys-Drash syndrome, congenital infections, such as cytomegalovirus (CMV), Epstein-Barr virus (EBV) and syphilis, and other uncommon disorders such as GallowayMowat syndrome and rare disorders of the glomerular basement membrane [1][2][3][4][5]. Rarely, idiopathic minimal change and focal segmental glomerulosclerosis cause nephrotic syndrome in late infancy [6].…”
Section: Introductionmentioning
confidence: 99%